Nomenclature report on rice WRKY's - conflict regarding gene names and its solution - Shen, Q. X. J.; Yu, D.Q.; Jeon, J.S.; Piffanelli, P.; Abbruscato, P.; Guo, Z.J.; Zhang, Y.J.; Itoh, T.; Lee, S.S.; Buell, C.R.; Nagato, Y.; McCouch, S.; et al. (Springer, 2012)
Since whole genome sequences of rice were made publically accessible, the number of articles onnew rice genes has increased remarkably. The Committee on Gene Symbolization, Nomenclature and Linkage(CGSNL) of the Rice Genetics Cooperative published the gene nomenclature system for rice and encouragedresearchers to follow the rules before publishing their results. The CGSNL provides an on-line registration systemfor newly identified rice genes to prevent conflicts and/or duplication of gene name in journal articles.Recently, the CGSNL surveyed genes in the rice WRKY family in published journal articles and foundseveral duplicated gene names.To discuss and resolve inconsistencies in WRKY gene nomenclature, the rice WRKY working groupwas established and redefined the nomenclature. This report announces the conclusion.